2011
DOI: 10.1038/jp.2011.149
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical arterial catheter insertion length: in quest of a universal formula

Abstract: Objective: The study was aimed at comparing the accuracy in length of insertion of umbilical arterial catheter in all new born groups stratified according to weight, by using two different methods, that is, Wright et al./ Case (Group I): (4 Â Body wt (BW) (kg)) þ 7; Shukla et al./Control (Group II): (3 Â BW (kg)) þ 9.Study Design: It was a randomized open label case control study in a Level III tertiary level Neonatal Intensive Care Unit over 9 months.Result: The babies in both the groups were similar in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
(14 reference statements)
1
4
1
Order By: Relevance
“…They found an 82% reduction in incorrect tip placement when using Wright’s formula (F7), with significant reduction in repositioning seen in all babies <1500 g 17. In our study, both formulae had similar accuracy (table 3) in infants <32 weeks.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…They found an 82% reduction in incorrect tip placement when using Wright’s formula (F7), with significant reduction in repositioning seen in all babies <1500 g 17. In our study, both formulae had similar accuracy (table 3) in infants <32 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…Kumar et al compared the formulae described by Wright (F7)13 and Shukla (F5)12 in a randomised controlled trial,17 which included 99 infants, stratified by birth weight. They found an 82% reduction in incorrect tip placement when using Wright’s formula (F7), with significant reduction in repositioning seen in all babies <1500 g 17.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of venous and arterial umbilical catheters correctly placed with Wright's formula was higher than Shukla's formula, both in patients < 1000 g and > 1000 g, which demonstrates the clinical superiority of this formula. The results of the present study showed no significant differences between the use of either Wright's or Shukla's formula for the correct placement of venous and arterial umbilical catheters in patients < 1500 g. Kumar et al 19 also compared these two formulas in 99 newborns stratified by birth weight and demonstrated an 82% reduction in incorrect placement of the tip of the umbilical arterial catheter when using Wright's formula, with a significant difference in catheter placement in neonates < 1500 g. There were 12 physicians involved in the insertion of catheters, verified by two independent physicians, and reviewed with a radiologist. In contrast, in the present study, catheter placement was verified at first intent by a single neonatologist and corroborated with a radiologist.…”
Section: Discussioncontrasting
confidence: 40%
“…The high position is recommended for umbilical arterial catheters (UACs); in the aorta, it is ideally between T6 and T9 vertebral bodies [ 11 ]. Despite a number of calculations based on both birth weight and external measurements for estimating correct positioning, there is a lack of consensus in the literature as to which is the most accurate [ 2 , 9 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%